Respostas
respondido por:
2
2x² - 1x - 3 = 0
a = 2 b = - 1 c = - 3
/\ = b² - 4ac
/\ = (- 1)² - 4 * 2 * (- 3)
/\ = 1 + 24
/\ = 25
x = - b + V¨¨¨¨/\
--------------------
2a
x = - (- 1) + V¨¨¨25
--------------------
2 * 2
x = 1 + 5
---------
4
x' = 1 + 5
4
x' = 6 : 4
x' = 1,5
x" = 1 - 5
4
x" = - 4 : 4
x" = - 1
Resposta: {1,5; - 1}
a = 2 b = - 1 c = - 3
/\ = b² - 4ac
/\ = (- 1)² - 4 * 2 * (- 3)
/\ = 1 + 24
/\ = 25
x = - b + V¨¨¨¨/\
--------------------
2a
x = - (- 1) + V¨¨¨25
--------------------
2 * 2
x = 1 + 5
---------
4
x' = 1 + 5
4
x' = 6 : 4
x' = 1,5
x" = 1 - 5
4
x" = - 4 : 4
x" = - 1
Resposta: {1,5; - 1}
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás